NGLY1 Deficiency Zebrafish Model Manifests Abnormalities of the Nervous and Musculoskeletal Systems - Mesika, Aviv; Nadav, Golan; Shochat, Chen; Kalfon, Limor; Jackson, Karen; Khalaileh, Ayat; Karasik, David; Falik-Zaccai, Tzipora C. (Frontiers in Cell and Developmental Biology, 2022)
Background: NGLY1 is an enigmatic enzyme with multiple functions across a wide range of species. In humans, pathogenic genetic variants in NGLY1 are linked to a variable phenotype of global neurological dysfunction, abnormal tear production, and liver disease presenting the rare autosomal recessive disorder N-glycanase deficiency. We have ascertained four NGLY1 deficiency patients who were found to carry a homozygous nonsense variant (c.1294G > T, p.Glu432*) in NGLY1. Methods: We created an ngly1 deficiency zebrafish model and studied the nervous and musculoskeletal (MSK) systems to further characterize the phenotypes and pathophysiology of the disease. Results: Nervous system morphology analysis has shown significant loss of axon fibers in the peripheral nervous system. In addition, we found muscle structure abnormality of the mutant fish. Locomotion behavior analysis has shown hypersensitivity of the larval ngly1(−/−) fish during stress conditions. Conclusion: This first reported NGLY1 deficiency zebrafish model might add to our understanding of NGLY1 role in the development of the nervous and MSK systems. Moreover, it might elucidate the natural history of the disease and be used as a platform for the development of novel therapies.